Tale of two neighbourhoods: biophysical and socio-economic vulnerability to climate change in Pinellas County, Florida. Issue 9 (1st September 2020) - Johns, Rebecca A.; Dixon, Barnali; Pontes, Rachelle
ABSTRACT: Defining vulnerability and identifying vulnerable areas and populations is critical to climate adaptation and resilience. Neighbourhoods are not homogeneous in terms of their socio-economic and physical vulnerability to flooding and other climate related impacts resulting in diverse challenges. Working with communities to better identify their concerns, liabilities, and strengths in the face of climate challenges will help build resiliency for all residents of the Tampa Bay area. This research identifies the weaknesses in knowledge, preparedness and ability to adapt in two communities in Pinellas County, Florida: examining a neighbourhood that is socio-economically vulnerable and a neighbourhood that experiences only physical (locational) vulnerability. We also identify opportunities for inclusive disaster planning, climate adaptation plans and to increase resiliency through long-term interactions between residents, community leaders, and local officials.